Dynamic Optimal Advertising Expenditure Strategies for Two Successive Generations of High Technology Products - Chanda, Udayan; Bardhan, A. K. (Modeling, Computation And Optimization, 2009)
Advertising plays a very important role in drawing consumer attention to new-products and in encouraging early adoptions. The problem of drawing optimal advertising plans for innovations have therefore has received a lot of attention from marketing managers and researchers. But there is need for further research on problems pertaining to new-products that are part of technological generations. This chapter deals with the determination of optimal advertising expenditure for two-generation consumer durables. The model considers intergenerational diffusion effect and also introduces a framework for modeling innovation diffusion for two competing generations.